PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI KONSUMEN DALAM TRANSAKSI E-COMMERCE SHOPEE - Alfajri Muhammad Chaniago; Mahmul Siregar; Joiverdia Arifiyanto (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Paylater has become popular because it is inclusive, flexible, and offers a simple registration process and various attractive promos. However, the increasing use of Paylater, such as SPayLater from Shopee, poses a risk of bad debt and personal data theft. Several cases, such as billing that does not comply with regulations and hacking of ShopeePay balances, show weaknesses in data security and management on the E-commerce platform. Therefore, research is needed to strengthen legal protection of consumer personal data in Shopee E-commerce transactions. The research uses a juridical-normative method with a legislative and literature approach. The results of this study are summarized in several conclusions, namely that legal protection of consumer personal data in e-commerce in Indonesia has developed, especially with the enactment of Law No. 27 of 2022. Although e-commerce service providers are obliged to maintain data confidentiality and security, challenges in implementing the law and consumer understanding of their rights still need to be overcome. From this conclusion, it is recommended that the government needs to strengthen supervision and enforcement of Law No. 27 of 2022 concerning Personal Data Protection by tightening security requirements and conducting periodic audits on e-commerce platforms.Keyword: Personal Data, Consumer, E-CommerceÂ Abstrak: Paylater menjadi populer karena inklusif, fleksibel, dan menawarkan proses pendaftaran yang sederhana serta berbagai promo menarik. Namun, meningkatnya penggunaan Paylater, seperti SPayLater dari Shopee, menimbulkan risiko kredit macet dan pencurian data pribadi. Beberapa kasus, seperti penagihan yang tidak sesuai aturan dan peretasan saldo ShopeePay, menunjukkan kelemahan dalam keamanan dan manajemen data di platform E-commerce. Oleh karena itu, diperlukan penelitian untuk memperkuat perlindungan hukum terhadap data pribadi konsumen dalam transaksi E-commerce Shopee. Penelitian menggunakan metode yuridis-normatif dengan pendekatan perundang-undangan dan literatur. Hasil penelitian ini dirangkum dalam beberapa kesimpulan yakni bahwa perlindungan hukum terhadap data pribadi konsumen dalam e-commerce di Indonesia telah mengalami perkembangan, terutama dengan adanya UU No. 27 Tahun 2022. Meskipun penyedia layanan e-commerce berkewajiban menjaga kerahasiaan dan keamanan data, tantangan dalam penerapan hukum dan pemahaman konsumen tentang hak-hak mereka masih perlu diatasi. Dari kesimpulan ini, disarankan pemerintah perlu memperkuat pengawasan dan penegakan UU No. 27 Tahun 2022 tentang Perlindungan Data Pribadi dengan memperketat persyaratan keamanan dan melakukan audit berkala pada platform e-commerce.Kata kunci: Data Pribadi, Konsumen, E-Commerce